Evaluasi Penerapan Manajemen Risiko di Direktorat Jenderal PQR Berdasarkan Pedoman Menteri - Pramayuningtyas, Arlin; Djakman, Chaerul Djakman (E-Jurnal Akuntansi, 2024)
The aim of this research is to evaluate the implementation of risk management at the Directorate General PQR based on Ministerial Guidelines. Ministerial guidelines are prepared as a reference basis for implementing risk management in order to establish a good quality of risk management. The method used in this research is by observing the secondary data such as any regulations and documents related to risk management and conducting interview. The result of this research shows that Directorate General PQR has not fully followed the rules set out in the Ministerial Guidelines in implementing risk management. There are several aspects of the Guidelines that have not been followed. Even though they have integrated the risk management process into their business process, the implementation of risk management is still a form of formality. Keywords: Risk; Risk Management; SPIP; Ministerial guidelines